Advertising principles : choice, challenge, change - Vanden Bergh, Bruce G. (NTC Business Books, 1999)
This book is divided into four parts: The Challenging Business of Advertising; The Challenge of Strategy in Marketing and Advertising; Media Strategy: Challenges and Choices; and The Challenge of Advertising Creativity.